Promising Antifungal Activity of Cedrela fissilis Wood Extractives as Natural Biocides against Xylophagous Fungi for Wood Artwork of Cultural Heritage - Vovchuk, Camila Sofia (2024)
Xylophagous fungi are able to thrive inside wood because they produce enzymes that can degrade it and cause significant damage. Due to this process, in the case of wood that forms part of the structure of a building or furniture, xylophagous fungi pose a serious problem that needs to be addressed, as they can compromise the integrity and durability of the wood. The aim of this work was to obtain extractives from Cedrela fissilis wood in order to conduct a preliminary evaluation of their antifungal activity against xylophagous fungi Trametes trogii (white rot), Pycnoporus sanguineus (white rot), and Chaetomium globosum (soft rot). The antifungal activity of the extractives was evaluated against these xylophagous fungi through tests of growth fungal colonies with the extractives in Petri dishes. All the evaluated extractives showed antifungal activity against all the fungi tested, demonstrating their potential use as natural biocides for wood artwork of Cultural Heritage.